The Effect of Music Listened to During the Recovery Period After Day Surgery on the Anxiety State and Vital Signs of Children and Adolescents - Atiye Karakul; Zehra Bahire Bolışık (Galenos Yayinevi, 2018)
Aim: To evaluate the effect of music listened to during the recovery period after day surgery on the anxiety state and vital signs of child and adolescent patients. Materials and Methods: A pre-test/post-test control group design. Intervention group (listened music) and control group were compared. Results: Patients (n=65) who listened to music demonstrated less anxiety than those who did not listen to music (n=65). Also, in the intervention group, pulse rates, diastolic and systolic blood pressure values and respiratory rates decreased after music therapy. Conclusion: Music listened to during the post-operative recovery period decreases the anxiety level of patients. Music therapy is a method which shows a positive effects on pulse rate, diastolic and systolic blood pressure values and respiratory rate without any side effects. Music therapy may be included in nursing care procedures applied to patients after day case surgery during the recovery period.